Implementation of a digital health tool for seizure video transfer in a pediatric epilepsy center: A prospective pilot study - Rahel M. Burger; Gadi Miron; Pascal Fenske; Cornelia Potratz; Angela M. Kaindl; Christian Meisel (Epilepsy & Behavior Reports)
Home videos are increasingly presented in clinical practice, and secure digital tools for clinical video sharing are urgently needed. This study evaluated the feasibility of a secure video-sharing digital platform in pediatric epilepsy diagnostics. We conducted a prospective pilot study that included 60 children (median age 5.5 years) with suspected seizures and their caregivers at a tertiary pediatric center. Participants were invited to submit videos of suspected events through a secure smartphone application. Videos were reviewed by an epileptologist and in parallel participants underwent standard diagnostic evaluation. Outcome measures included video quality, concordance of video assessment with diagnostic workup, and user evaluation questionnaires. Of recruited participants, 16 (26.7 %) used the app to submit 81 videos (median 5.1 videos per patient), with 94 % (76/81 videos) having sufficient quality for meaningful clinical review. Among these participants, 11 (68.8 %) had confirmed epilepsy as their final diagnosis, while 5 (31.2 %) did not. Expert review classified 48.1 % of videos as likely epileptic events, with generalized tonic-clonic seizures being most common (24.7 %). Concordance between submitted videos and final clinical diagnosis was demonstrated in 68.8 % of cases, with higher concordance significantly related to the number of videos submitted (mean 6.4 vs. 2.2 videos per patient, p = 0.04). User evaluation showed favorable ratings for app usability (mean score 5.4/7). This study demonstrates the feasibility of secure digital video transfer in pediatric epilepsy diagnostics, emphasizing the importance of multiple video submissions for accurate diagnosis. Future implementation should address barriers to wider adoption and investigate clinical impact.